2010
DOI: 10.1111/j.1601-0825.2009.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase of microRNAmiR-31level in plasma could be a potential marker of oral cancer

Abstract: This study concluded that plasma miR-31 could be validated a marker of OSCC for diagnostic uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
210
3
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(227 citation statements)
references
References 32 publications
7
210
3
7
Order By: Relevance
“…Changes in miRNA expression have been observed in a variety of human tumors, including breast (5), prostate (6), hepatocellular (7), colorectal (10) and oral cancer (11), chronic lymphocytic leukemia (12) and bladder cancer (13) (Table Ⅰ). miRNAs are involved oncogenesis, disease progression, invasion and metastasis, and are associated with patient prognosis (4,14).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in miRNA expression have been observed in a variety of human tumors, including breast (5), prostate (6), hepatocellular (7), colorectal (10) and oral cancer (11), chronic lymphocytic leukemia (12) and bladder cancer (13) (Table Ⅰ). miRNAs are involved oncogenesis, disease progression, invasion and metastasis, and are associated with patient prognosis (4,14).…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of tumor-derived miRNAs in the plasma is an important approach for the blood-based detection of human cancer (12). Numerous studies have indicated that plasma miRNAs have potential diagnostic or prognostic value in various types of tumors, including breast cancer (14), leukemia (29), gastric cancer (30), oral cancer (31) and colon cancer (32).…”
Section: Discussionmentioning
confidence: 99%
“…;Bae, S.D., 2011). Furthermore, some miRNAs (31, 184) showed high plasmatic level in OSCC, decreasing dramatically after tumor excision Kao, S.Y., 2010). On the other hand, miRNAs let-7b, 26, 100, 107, 124, 125, 133, 138, 139, 200, 375 decrease in cancer.…”
Section: Alteration In Intracellular Plasmatic Salivary Levelsmentioning
confidence: 99%